Chest radiographic lateral soft-tissue thickness changes after complete anit-tuberculosis treatment in adults (2016)
Background: Pulmonary tuberculosis (PTB) has 95-98% of its mortality in developing countries. It is associated with marked weight loss which can be evident at the lateral soft-tissue thickness on chest radiographs. Objective: To determine the pattern of lateral soft- tissue thickness changes and gender predisposition on chest radiographs in PTB patients and after complete anti-TB treatment. Methodology: This prospective study was conducted over a 6 month period at the Radiology Department of Ahmadu Bello University Teaching Hospital, Zaira. Two hundred adults who were bacteriologically proven to have PTB were consecutively recruited into the study as cases, aged 18-70 years and followed up after 6 months of complete anti-TB treatment and found to be asymptomatic bacteriologically sputum negative. Their lateral soft-tissue thickness on the chest radiographs was measured. Results: The mean and standard deviation of pretreated and posttreated PTB patient was 12.66+2.63mm and 21.13 + 2.56 mm, respectively (p<0.0001). However, significant increase is noted in lateral soft-tissue thickness after complete anti- TB treatment (P<0.001) and female sex (P+0.001). Conclusion: Lateral soft- tissue thickness reduction was seen in PTB patients and significant increase was observed after complete anti-TB treatment.